Characterization of pharmacotherapy for opportunistic infections and comorbidities among hospitalized patients with HIV/AIDS at a hospital from 2018 to 2023 - Pertuz Pizarro, Cristian David (2025)
Objective: To characterize the pharmacotherapy for opportunistic infections and comorbiditiesamong hospitalized patients with HIV/AIDS at Hospital Universidad del Norte from 2018 to June2023. Materials and methods: A descriptive, retrospective, cross-sectional study, focusing on thecollection of clinical data from 2018 to June 2023 and using a non-experimental research approach. Data collection was conducted at Hospital Universidad del Norte from patients diagnosed with HIV/AIDS, which served as the target population. A convenience sample of 109 patients was selected based on predefined inclusion criteria, which requiredparticipants to be over 18 years of age and have a hospital stay longer than four days. Clinical data were collected from medical records and analyzed using IBM SPSS Statistics and Microsoft Excel. Results: The mean age of the patients was 43.6 years, withan average hospital stay of 14.9 days per patient. Fluconazole was the most commonly prescribed medication for the treatment of opportunistic infections, used by 58.5 % of the study population. For comorbidities, amlodipine was the most frequently prescribed medication, used by 23.1 % of the study population. The most prevalent opportunistic infections were oropharyngealcandidiasis (15.43 %), followed by Pneumocystis jirovecii pneumonia (PJP) (12.75 %), tuberculosis (11.40 %) and toxoplasmosis (10.73 %). The most common comorbidities were hypertension (28.94 %) and major depressive disorder (18.42 %). The economic impact of medication-related problems (MRPs) and negative medication-related outcomes (NMROs) amounted to associated costs of $1,223,717 and $5,008,521, respectively. Conclusions: The age group most susceptible to opportunistic infections was between 40 and 50 years, with males being the most affected. Most patients were in the AIDS phase, particularly those diagnosed based on medical history. Fluconazole stood out as the most commonly used medication for treating opportunistic infections, followed by the combination of both trimethoprim + sulfamethoxazole and rifampicin + isoniazid + pyrazinamide + ethambutol. In the treatment of comorbidities, amlodipine was the most frequently prescribed medication, followed by losartan, mirtazapine, levetiracetam and sertraline.